BTEX Concentrations and Associated Health Risks at Urban Vegetative Sites in Delhi, India. Issue 4 (2nd October 2019) - Kashyap, Prabhat; Kumar, Amit; Kumar, Krishan
Abstract: Benzene, toluene, ethylbenzene, and xylene (BTEX) compounds are known for their toxic effects. The ambient BTEX levels were studied at various urban vegetative locations of Delhi to assess the health risks involved. The average concentrations were higher for toluene and xylene among BTEX compounds. The cancer risks for benzene exceeded the benchmark limits of USEPA and WHO. The study suggests that the vegetative areas in Delhi are not safe for public health and regulatory bodies need to initiate some action.